Surgical Outcomes of Patients with Sacroiliac Joint Pain: An Analysis of Patients with Poor Results Regarding Activities of Daily Living - Kurosawa, Daisuke (Spine Surg Relat Res, 2021)
INTRODUCTION: Sacroiliac joint (SIJ) arthrodesis is the last resort for patients with severe SIJ pain. However, this technique does not always provide good outcomes regarding activities of daily living (ADL). This study aims to reveal the preoperative clinical features associated with poor outcomes of SIJ arthrodesis. METHODS: Twenty-six consecutive patients who underwent SIJ arthrodesis between 2009 and 2018 were evaluated. Good-outcome was defined as ≥30% improvement in ADL, quantified by the Roland-Morris Disability Questionnaire (RDQ). The good-outcome group (17 patients; 10 men and 7 women, 42.5±8.4 years old) and the poor-outcome group (9 patients; 1 man and 8 women, 47.0±17.9 years old) were compared to identify the preoperative clinical features of poor surgical outcomes. RESULTS: No significant differences were observed between the two groups regarding age, preoperative RDQ score, time between onset and the confirmed diagnosis of SIJ pain, and the time between diagnosis and surgical treatment. The following preoperative clinical features associated with poor surgical outcomes were identified: female sex, pain in multiple regions, walking with a cane, and the use of a wheelchair before surgery (P<0.05). CONCLUSIONS: The present study demonstrated that poor postoperative outcomes in patients with severe SIJ pain were associated with the following preoperative clinical features: female sex, pain in multiple regions, walking with a cane, or use of a wheelchair. Ample attention is warranted in patients with such features who are indicated for surgical treatments.